A Sensory Reading of Rabanus Maurus' De Universo - Rodríguez, Gerardo Fabián (2019)
Rabanus Maurus was an outstanding character, in many ways representative ofthe Carolingian times. He was even deemed the greatest scholar of its times. Hisknowledge about the Scriptures, patristics, cannon law, and liturgy was unparalleled.Rabanus Maurus' work dealt with all areas of knowledge, both sacred and profane. De Universo-originally known as De natura rerum'is a clear example of the scholarly interest in the organization of encyclopedic knowledge and manuals characteristic of the High Middle Ages, and presents a hierarchical organization of the senses that is key to the understanding of the sensory world during the 8th and 9th centuries.